Role of Dobutamine Stress Echocardiography in the Evaluation of Patients Undergoing Noncardiac Surgeries in the Contemporary Era - Tanu Chaudhary; Manish Bansal; Ravi R. Kasliwal (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
Objective: Dobutamine stress echocardiography (DSE) is a widely used diagnostic modality for preoperative cardiac risk assessment in patients undergoing major noncardiac surgeries. However, its role in facilitating safe noncardiac surgery in the contemporary era needs to be evaluated. Materials and Methods: A total of 1283 participants (mean age – 63.8 years and 54.9% males) undergoing DSE for preoperative cardiac evaluation before nonemergent, noncardiac, major surgeries were included. DSE findings were recorded, and the Revised Cardiac Risk Index or Lee’s score was also calculated. The patients were followed up for in-hospital adverse cardiac events. Results: DSE showed evidence of inducible myocardial ischemia in 19 (1.5%) patients, whereas Lee’s score was elevated (>3) in 43 (3.4%) patients. The overall in-hospital event rate was 0.7%. Among 1264 patients with normal DSE, 5 (0.4%) had a perioperative cardiac event (negative predictive value 99.6%). Of the 19 patients with abnormal DSE, all underwent coronary angiography which was abnormal in 16 patients. Of these 16 patients, 4 had a perioperative cardiac event. A Lee’s score value >3 had a sensitivity of 68.4% (95% confidence interval [CI] - 43.5–87.4), specificity of 97.6% (95% CI - 96.6–98.4), positive predictive value of 30.2% (95% CI - 21.4–40.9), and negative predictive value of 99.5% (95% CI - 99.1–99.8) for predicting abnormal DSE. Conclusion: Our study reinforces the clinical utility of DSE in facilitating major, nonemergent, noncardiac surgeries in a contemporary setting in India. A normal DSE had a very high negative predictive value for an adverse cardiac event, whereas an abnormal DSE identified the population at high risk for perioperative cardiac events requiring appropriate risk mitigation strategies.